2017
DOI: 10.1016/j.jor.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Single incision pediatric flexible intramedullary tibial nailing

Abstract: Background: There has been a trend towards flexible intramedullary nailing for unstable tibial shaft fractures in the pediatric population, traditionally, utilizing a 2-incision technique with passage of one nail medially and one nail laterally. Our study aims to compare a single incision approach for flexible nailing of unstable tibial shaft fractures in pediatric patients to the traditional 2-incision approach. Methods: Patients were selected for operative fixation if they had a length unstable tibial shaft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This technique could be used and alleviate the difficult decision in determining the borderline “too young” adolescent patient with open physis to receive a reamed intramedullary nail, where the risk of physis arrest still is uncertain 19. The technique would allow for relative stability with a load-sharing construct and minimally invasive aspects of EIN while decreasing the morbidity associated with open plating 1. Recent studies have shown that elective hardware removal risks may not outweigh the benefit but is required in pediatric patients for continued growth 20.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This technique could be used and alleviate the difficult decision in determining the borderline “too young” adolescent patient with open physis to receive a reamed intramedullary nail, where the risk of physis arrest still is uncertain 19. The technique would allow for relative stability with a load-sharing construct and minimally invasive aspects of EIN while decreasing the morbidity associated with open plating 1. Recent studies have shown that elective hardware removal risks may not outweigh the benefit but is required in pediatric patients for continued growth 20.…”
Section: Discussionmentioning
confidence: 99%
“…19 The technique would allow for relative stability with a load-sharing construct and minimally invasive aspects of EIN while decreasing the morbidity associated with open plating. 1 Recent studies have shown that elective hardware removal risks may not outweigh the benefit but is required in pediatric patients for continued growth. 20 These risks could be lessened with reopening of a smaller less invasive incisions with EIN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations